Homosexual men, ageing and internalized homophobia - Antunes, Pedro Paulo Sammarco (2017)
Homophobia can be expressed as the antipathy, contempt, prejudice, dislike, hatred, verbal and physical abuse or even death (hate crime) in relation to LGBT (lesbian, gay, bisexual, and transgender) people. When it happens in homosexuals themselves, it is scientifically defined as internalized homophobia. This article aims to discuss possible impacts of internalized homophobia in elderly homosexual men.Keywords: Homosexual men; Aging; Internalized homofobia.